Some utilitarian objects from Edo North and the Northern Edo and Benin artistic relationship (2016)
The history of Northern Edo land, Nigeria has been subsumed in the history of Benin kingdom and indeed, due to oversimplification, northern Edo history has been reduced to the history of Benin. Presently, the only available means to salvage the history of Northern Edo land remains the art objects collected by Northcote Thomas from Edo land, between 1908 and 1914. The collection is now domiciled at the Museum of Archaeology and Anthropology (MAA) of the University of Cambridge, unutilized. The paper therefore undertook a comparative iconographic study of selected objects from the Thomas' collection with Benin art, in an attempt to make some more specific and perhaps categorical statements about a possible Benin-Northern Edo artistic relationship. Some of the works analysed from the collection include kola nut bowls from Otuo, Uzebba decorated kola nut bowls, igbede bowls, and Okpe decorated lad] e out of others: Evidently these artworks are prestigious objects, yet the Edo north community is devoid of such powerful central administrative system that could be in demand of such objects. This raises questions about the peopling of the region. From the available evidential materials, under consideration, it was then postulated that there could have been the possibility of north-south movement and a later south-north movement in that region, which has caused a thinning-out of the culture that produced the Thomas' collection. The paper concluded that the makers of the selected objects from the Thomas' collection might be different from the present day inhabitants of the region.